PENERAPAN REWARD DAN PUNISHMANT DALAM MEMBENTUK DISIPLIN SANTRI DI PONDOK PESANTREN PUTRA Al WAHABIYYAH 1 BAHRUL ULUM TAMBAKBERAS JOMBANG - Mohammad Lutfi As'ari; Machnunah Ani Zulfah (JoEMS (Journal of Education and Management Studies), 2020)
In the perspective of Islamic education, reward and punishment which contains the meaning of giving punishment to a student / student who made a mistake or violation; and vice versa giving awards to students who are considered to have contributed or showed achievement, is a systematic educational pattern that has been taught in Islam. The Qur'an globally has signaled the existence of punishment and respect for each person's deeds. So from these assumptions, the writer was interested in making a study entitled: Application of reward and punishment in forming santri discipline in pondok pesantren putra al-wahabiyyah 1. This study aims to find out how the picture of the implementation of reward and punishment in pondok pesantren putra Al-wahabiyyah 1. Research this using a qualitative descriptive approach, the presence of researchers in the field is very important. The researcher acts directly as an instrument and as a data collector resulting from in-depth observations and is actively involved in the research. Data in the form of words were obtained from the informants, while additional data in the form of documents. Data analysis is done by examining existing data, then reducing data, presenting data and drawing conclusions and the final stage of data analysis is conducting data validity using persistence of triangulation observations.